e-INFRASTRUCTURES: CATALYSTS OF A NEW SCIENTIFIC RENAISSANCE. - Campolargo, Mário (Computer (00189162), 2009)
This article discusses the potential for data-intensive research methods that depend on high performance computing to fundamentally change scientific practices. The European investment in electronic infrastructure including computing grids and supercomputing systems is described. The integration of Web 2.0 interfaces with the data-intensive computing systems described is presented as an opportunity to foster transparency and communication in science.